2016
DOI: 10.7196/samj.2016.v107.i1.10924
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous malignancies in the Northern Cape Province of South Africa: A retrospective histopathological review

Abstract: Background.Excessive sun exposure and a high prevalence of HIV increase skin cancer risk in South Africa (SA). Objective. To describe the nature and extent of skin cancers presenting in the public and private health sectors of the Northern Cape Province of SA. Methods. A retrospective analysis of histologically confirmed new primary cutaneous malignancies from 1 January 2008 to 31 December 2012 was conducted using public and private health sector databases. Types, quantity and distribution of common invasive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 21 publications
9
25
2
Order By: Relevance
“…KS accounted for 7% of all skin cancers diagnosed and was the most frequent skin cancer in the black population. is finding supports data from the Northern Cape Province of South Africa that showed KS to account for 6.5% of all skin cancers and occurring more commonly in the black population [26]. When compared to data from sub-Saharan African, Nthumba et al reported KS to represent 25% of skin cancers diagnosed in Kenya in 2008 [24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…KS accounted for 7% of all skin cancers diagnosed and was the most frequent skin cancer in the black population. is finding supports data from the Northern Cape Province of South Africa that showed KS to account for 6.5% of all skin cancers and occurring more commonly in the black population [26]. When compared to data from sub-Saharan African, Nthumba et al reported KS to represent 25% of skin cancers diagnosed in Kenya in 2008 [24].…”
Section: Discussionsupporting
confidence: 82%
“…e largest review reported SCC and KS to constitute 44% and 25% respectively of the cutaneous malignancies and BCC's only 7% [24,25]. Interestingly a recent study done in the Northern Cape Province of South Africa also found that 45.4% of skin cancers diagnosed were SCC while only 27.8% were BCC [26]. ese differences in skin cancer frequency can most likely be attributed to the difference in population distribution in the Western Cape when compared to that of other sub-Saharan African countries and other parts of South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…[3,5,6] In a large German cohort (2 050 ALM patients) the mean Breslow thickness was 3.08 mm (median 2.2 mm), [5] which was in keeping with other studies on ALM from developed countries that reported a mean Breslow thickness between 2.51 mm and 2.8 mm at presentation. [6,15] York et al [19] reported a mean Breslow depth of 4.13 mm in ALMs diagnosed in the Northern Cape Province of SA. In the current study, mean Breslow thickness at diagnosis was 5.2 mm (median 4.2, range 0 -22), suggesting that patients present much later than the norm in developed countries.…”
Section: Researchmentioning
confidence: 99%
“…Studies have focused on a single population group [5,6] or a single province. [5][6][7] Skin cancer incidence data were last reported for 2000 -2004 (inclusive), showing differences in incidence rates and body sites by population group and gender. [8] Melanoma is more common in fair than dark individuals, but does occur in black Africans.…”
Section: Researchmentioning
confidence: 99%
“…[9][10][11][12] Several studies have reported worse disease outcomes for melanoma patients with darker skin types [10,12,13] and melanoma of hands and feet. [1,14] Objectives Variation in reported SA incidence rates of melanoma [5,[7][8][9] makes it difficult to form robust conclusions. Incidence rates ranging from 11.8 per 100 000 in white females in Northern Cape Province [7] to 69 per 100 000 for the white population in Western Cape Province have been reported.…”
Section: Researchmentioning
confidence: 99%